LEGAL LIABILITY OF THE MEMBERS OF THE BOARD OF DIRECTORS IN JOINT-STOCK COMPANIES - Seyman, Seda (PEOPLE: International Journal of Social Sciences, 2018)
The second book regulates trade companies including articles 124 to 644 of the Turkish Commercial Code numbered 6102. Classification of trading companies in the Turkish Commercial Code; joint stock companies, collective companies, limited companies, commandite companies and cooperative companies. The board of directors is a necessary board for joint stock companies, and the company in general continues to operate with the decisions taken in this board. In this regard, the external affair activities of joint stock companies, with resolutions of the board of directors is executed. When the obligations non performance, the members of the Board of Directors become liable both legally and criminally. The purpose of article, Legal Liability of The Members of The Board of Directors in Joint Stock Companies is the issue and discussed; a study has been carried out within the framework of the purpose, scope and consequences of the legal responsibility.